AKTIVITAS ANTIMALARIA PENGHAMBATAN POLIMERISASI HEME EKSTRAK ETANOL DAUN JAMBU BIJI (Psidium guajava) DAN DAUN PEPAYA (Carica papaya) - M. Arifuddin; Mahfuzun Bone; Rolan Rusli; Hadi Kuncoro; Islamuddin Ahmad; Laode Rijai (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
In an effort to find new sources of medicinal plants as antimalarials based on ethnobotany knowledge from generation to generation. Therefore, tested the inhibition of heme polymerization from 70% ethanol extract of papaya leaves (Carica papaya) and Guava (Psidium guajava) leaves. The data obtained were calculated by IC50 using SPSS 22 obtained that 70% ethanol extract of Pepaya leaves (Carica papaya) and Jambu Biji leaves (Psidium guajava) had antimalarial activities of 7,914 and 8,794 mg/ml respectively and their had the potential to be developed in more research further as antimalarial.